Simulation of Vehicle Distance Detection for Traffic Order - Baldemor, Milagros Racacho (Talenta Publisher, 2024)
The use of ultrasonic sensors, especially HC-SR04, in microcontroller projects is expanding thanks to its ability to accurately detect distance. In this final project, the HC- SR04 is connected to an ESP32 to measure the distance of an object and provide feedback in the form of sound when the object approaches the sensor within a certain distance. The HC-SR04 sensor works by emitting ultrasonic waves and measuring the time it takes for the waves to reflect back to the sensor. The ESP32, as the microcontroller connected to the sensor, processes this time data to calculate the object's distance from the sensor. When the distance of the object is below a predetermined threshold, the ESP32 will activate the buzzer as a sound signal. This implementation can be applied in various systems, for this test we used it on the zebra crossing system automatically. The test results show that this system is able to detect distance with sufficient accuracy and provide a fast and consistent sound response according to changes in object distance.